2011
DOI: 10.1590/s1517-83822011000400004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antifungal activity in essential oil of the Syzygium aromaticum (L.) by extraction, purification and analysis of its main component eugenol

Abstract: Antifungal properties of some essential oils have been well documented. Clove oil is reported to have strong antifungal activity against many fungal species. In this study we have evaluated antifungal potential of essential oil of Syzygium aromaticum (L.) against some common fungal pathogens of plants and animals namely, Fusarium moniliforme NCIM 1100, Fusarium oxysporum MTCC 284, Aspergillus sp., Mucor sp., Trichophyton rubrum and Microsporum gypseum. All fungal species were found to be inhibited by the oil w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
3
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(93 citation statements)
references
References 18 publications
1
84
3
5
Order By: Relevance
“…TLC analysis showed that Eugenol was present as a main component in the three EON tested concentration, as the colored zone showed the same R f value comparable with eugenol standard. Similar fractionation was performed using TLC analysis to identify the active antifungal components in clove oil (Park et al 2007;Rana et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…TLC analysis showed that Eugenol was present as a main component in the three EON tested concentration, as the colored zone showed the same R f value comparable with eugenol standard. Similar fractionation was performed using TLC analysis to identify the active antifungal components in clove oil (Park et al 2007;Rana et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is very important to underline that the use of plants and other botanical preparations are used, since ancient times, by primitive societies, due to healing properties and therapeutic and psychotherapeutic benefits. It is important to address the fact that plants are widely used to obtain a large variety of drugs, being used in folk medicine for a long time [26][27][28][29][32][33][34][35]. Concerning that plants represent an economic, easily and which are accessible for all of people, they can be used into a variety of diseases, constituting an excellent source of biomolecules able to act like natural antifungal agents and, at the same time, to encourage the search for other alternative treatments.…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…More and more, people worldwide use medicinal plants as first priority to maintain a good health, to prevent or even treat some health conditions. Linked to this, some studies have been conducted, using a wide variety of plants, towards the identification of bioactive molecules, their properties and mechanisms of action (Agarwal et al, 2010;Alves-Silva et al, 2013;Asgarpanah and Kazemivash, 2012;Asl and Hosseinzadeh, 2008;Bakkali et al, 2008;Kanafani and Perfect, 2008;Rana et al, 2011;Sher, 2009;Shojaii and Fard, 2012;Silva et al, 2011b;Singh et al, 2010). In fact, natural matrices, in particular, plants, are extremely rich sources of biomolecules that have sparked an increasing interest for scientific researchers, in different areas of knowledge.…”
Section: Plants As a Rich Source Of Bioactive Compoundsmentioning
confidence: 99%